The Impact of Financial Distress, Information Technology, and Macroeconomics on Stock Returns of State-Owned Enterprises Listed on the Indonesia Stock Exchange (IDX) - Nadiya Destriantari; Agus Zahron Idris (Harmoni Economics: International Journal of Economics and Accounting, 2025)
This study aims to analyze the impact of financial distress, measured using the Springate S-Score, information technology represented by IT spending, and macroeconomic factors such as interest rates and exchange rates on the stock returns of State-Owned Enterprises (SOEs) listed on the Indonesia Stock Exchange during the period of 2019-2023. The research method employed is multiple linear regression analysis with a quantitative approach, utilizing secondary data from annual financial reports of SOEs selected through purposive sampling. The results show that financial distress, as proxied by the Springate S-Score, has a significant positive effect on stock returns, while information technology does not have a significant impact on stock returns. The macroeconomic factor, exchange rate, has a significant positive effect on stock returns, whereas interest rates show no significant relationship. Overall, these findings provide insights for investors and SOE management in formulating more effective investment strategies and operational decisions in the capital market.